Optimum Arrangement of Reactive Power Sources While Using Genetic Algori - A. M. Gashimov; R. N. Rakhmanov; S. T. Rakhmanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Reduction of total losses in distribution electricity supply network is considered as an important measure which serves for improvement of efficiency of electric power supply systems. This objective can be achieved by optimum distribution of reactive power sources in proper places of distribution electricity supply network. The proposed methodology is based on application of a genetic algorithm. Total expenses for installation of capacitor banks, their operation and also expenses related to electric power losses are considered as an efficiency function which is used for determination of places with optimum values of capacitor bank power. The methodology is the most efficient for selection of optimum places in the network where it is necessary to install capacitor banks with due account of their power control depending on a switched-on load value in the units.